2005
DOI: 10.1161/01.cir.0000159262.18512.46
|View full text |Cite
|
Sign up to set email alerts
|

Increased Mortality and Aggravation of Heart Failure in Estrogen Receptor-β Knockout Mice After Myocardial Infarction

Abstract: Background-Lower mortality rates among women with chronic heart failure than among men may depend in part on the action of female sex hormones, especially estrogens. The biological effects of estrogens are mediated by 2 distinct estrogen receptor (ER) subtypes (ER␣ and ER␤). The present study was undertaken to determine the role of ER␤ in the development of chronic heart failure after experimental myocardial infarction (MI of heart failure, and contributes to impaired expression of Ca 2ϩ -handling proteins in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
95
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(101 citation statements)
references
References 47 publications
6
95
0
Order By: Relevance
“…33 Systemic deletion of ER increased the mortality of myocardial infarction. 34 In the present study, we investigated the expression of cardioprotective substances such as ANP, BNP and HSP70 at the end of IMO stress for 30 min, and found that there was an upregulation of ANP and HSP70 mRNA but not BNP mRNA in OVX + E compared with OVX. In fact, the expression of ANP, BNP and HSP70 mRNA was also increased in response to IMO stress.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…33 Systemic deletion of ER increased the mortality of myocardial infarction. 34 In the present study, we investigated the expression of cardioprotective substances such as ANP, BNP and HSP70 at the end of IMO stress for 30 min, and found that there was an upregulation of ANP and HSP70 mRNA but not BNP mRNA in OVX + E compared with OVX. In fact, the expression of ANP, BNP and HSP70 mRNA was also increased in response to IMO stress.…”
Section: Discussionmentioning
confidence: 86%
“…The protective effects of estrogen in the heart have been demonstrated in several pathological conditions such as ischemia-reperfusion injury 33,34 and pressure-overload hypertrophy. 35 The ER -selective agonist but not the ERselective agonist reduced the infarct size of an ovariectomized rabbit heart.…”
Section: Discussionmentioning
confidence: 99%
“…61,62 It appears, however, that ER␤ mediates the sex difference in response to pressure overload 63 and attenuates the transition to heart failure. 64 Female ER␤-null mice show a more rapid development of CHF and increased mortality rate after MI. 64 Although similar studies in mice that lack aromatase (the enzyme that converts testosterone to estradiol) have not been performed, increasing evidence indicates that treatment with an aromatase inhibitor leads to significant cardiovascular risk.…”
Section: Estrogen Receptors and The Heartmentioning
confidence: 99%
“…64 Female ER␤-null mice show a more rapid development of CHF and increased mortality rate after MI. 64 Although similar studies in mice that lack aromatase (the enzyme that converts testosterone to estradiol) have not been performed, increasing evidence indicates that treatment with an aromatase inhibitor leads to significant cardiovascular risk. 65 Estrogen can also initiate cellular changes through nongenomic mechanisms.…”
Section: Estrogen Receptors and The Heartmentioning
confidence: 99%
“…LV preload was assessed by end-diastolic pressure (LVEDP, mm Hg), contractility by ϩdP/dt max (mm Hg/sec) and (ϩdP/dt max )/IP which is the peak rate of rise in ventricular pressure normalized to instantaneous developed pressure and relaxation by -dP/dt max (mm Hg/sec); the time constant of isovolumic relaxation (, ms) was also determined. 16 Dobutamine was administered IV using a jugular vein. …”
mentioning
confidence: 99%